EVALUASI DAYA HASIL GENOTIPE JAGUNG F14 DI LAHAN GAMBUT - Yusuf, Yusuf; Hidayat, Hidayat; Arifin, Nur (Fakultas Pertanian Universitas Tanjungpura, 2019)
This research was done to evaluate yield potential of five F14 genotypes of maize in peat soil. This research was done in Rasau Jaya II peat soil since January until June 2018. The experiment used Randomized Block Design (RBD), consisted of five F14 genotypes that is B, C, D, E, F and one control variety, Arjuna (A). Each treatments were grouped into five block. The results showed that the yield of five F14 genotypes was relatively the same as the control variety. Genotypes showing good yield on Rasau Jaya II peat soil are genotypes F, B and C.